2014
DOI: 10.1159/000358564
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Assessment of the Diaphragm in Chronic Obstructive Pulmonary Disease Patients: Relationships with Pulmonary Function and the Influence of Body Composition - A Pilot Study

Abstract: Background: Skeletal muscle weakness with loss of fat-free mass (FFM) is one of the main systemic effects of chronic obstructive pulmonary disease (COPD). The diaphragm is also involved, leading to disadvantageous conditions and poor contractile capacities. Objectives: We measured the thickness of the diaphragm (TD) by ultrasonography to evaluate the relationships between echographic measurements, parameters of respiratory function and body composition data. Methods: Thirty-two patients (23 males) underwent (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 35 publications
(46 reference statements)
2
76
1
2
Order By: Relevance
“…The strong positive correlation between diaphragm contractility (TF) and COPD severity (FEV 1 %) detected in this study signifies that with progression of COPD, increased airflow obstruction caused dynamic air trapping; consequently, hyperinflation-induced diaphragm shortening developed, which places the diaphragm on a suboptimal position on its forcelength relationship that limits its ability to contract, which eventually leads to diaphragm muscle thinning. In the same context, Smargiassi et al (6) reported that the diaphragm thickness and TR were related to FEV 1 and FVC with no significant difference in diaphragm thickness between GOLD A, B, C, D groups. Another study reported a positive correlation between diaphragm thickness and FEV 1 % in mild COPD group but not in moderate and severe COPD groups (8).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The strong positive correlation between diaphragm contractility (TF) and COPD severity (FEV 1 %) detected in this study signifies that with progression of COPD, increased airflow obstruction caused dynamic air trapping; consequently, hyperinflation-induced diaphragm shortening developed, which places the diaphragm on a suboptimal position on its forcelength relationship that limits its ability to contract, which eventually leads to diaphragm muscle thinning. In the same context, Smargiassi et al (6) reported that the diaphragm thickness and TR were related to FEV 1 and FVC with no significant difference in diaphragm thickness between GOLD A, B, C, D groups. Another study reported a positive correlation between diaphragm thickness and FEV 1 % in mild COPD group but not in moderate and severe COPD groups (8).…”
Section: Resultsmentioning
confidence: 92%
“…Inspiratory muscles' weakness in COPD is caused by hyperinflation and generalized muscle weakness that is caused by deconditioning, malnutrition, electrolyte disturbances, cardiac failure, along with systemic inflammation (5) and long-term administration of steroids (6). Additionally, in patients with COPD, the diaphragm works against an increased work load due to airflow limitation and geometrical changes in the thorax as a result of pulmonary hyperinflation (4).…”
mentioning
confidence: 99%
“…Muscle wasting is called a significant determinant of mortality in severe COPD patients. Recent studies suggest that loss of fat free mass (FFM) is more accurate than BMI for predicting severity of the disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…Studies dealing with inspiratory muscle weakness in COPD patients focus mostly on diaphragm since it is the principal generator of tidal volume [3]. US findings of diaphragm muscle in COPD patients is not concluded yet because of the varying results [3][4][5][6][7].These studies address the structure and the motion of the diaphragm [4]. The impairment of diaphragm is suggested to be an important factor which is associated with alterations in the principal pulmonary function parameters such as FEV1 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Smargiassi et al [10] have shown the possible role of echographic measurement of diaphragm thicknesses in transthoracic approach at the zone of apposition (the area in which diaphragm adheres to thoracic wall) in COPD patients. It has been demonstrated that the measurement of both thickness and thickening of the diaphragm at the end of a maximal inspiration might be a useful tool to estimate lung hyperinflation when adjusted for fat-free mass (FFM).…”
Section: Introductionmentioning
confidence: 99%